MOTIVASI BELAJAR SISWA TERHADAP PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SELAMA MASA NEW NORMAL PADA SISWA KELAS VIII MTSN 4 KAMPAR - Afli Renaldi; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: After direct observations in the field, it was impressed that the Learning of Physical Education on Sports and Health During the New Normal Period for Grade 9 Students at MTsN 4 Kampar had not been implemented effectively. That is, physical education learning at the school is still far from other fields of study. Likewise, the students in participating in learning seem less motivated to take part in physical education learning. It is as if the physical education learning is just a spare time filler and complement. When learning takes place the students also look not serious and often play truant for no apparent reason. The purpose of this study was to find out and at the same time describe students' motivation in learning physical education, sport and health during the new normal period in class VIII MTsN 4 Kampar students. The target population is the number of students who are always actively involved in participating in the physical education learning process as many as 91 male students and 97 female students spread from class VIII A to class VIII F. From the population, 20% of the population is taken randomly or with the Random Sampling technique. Thus obtained a sample of 38 people. Data is taken through the distribution of questionnaires. Based on the findings of research on students' intrinsic and extrinsic motivation towards learning physical education, sports and health at MTsN 4 Kampar, it can be concluded that the intrinsic motivation of students at MTsN 4 Kampar obtained an achievement level of 84.70%, classified as